Nanoemulsi Campuran Minyak Flower Musk dan Minyak Atsiri Lili Menggunakan Surfaktan PEG 40 Hydrogenated Castor Oil dan Uji Stabilitas Ukurannya - Angelita, Flora; Saragih, Horasdia (Universitas Andalas, 2025)
The use of alcohol-based perfumes often causes skin irritation, prompting the development of water-based perfumes. However, the challenge is that essential oils, the main ingredient in perfumes, are hydrophobic. Nanoemulsion technology offers a solution to this problem. Perfume ingredients are formulated in nanometer sizes, then encapsulated with a surfactant so that they can be dispersed homogeneously in water. This study aims to develop a nanoemulsion mixture of flower musk oil and lily essential oil as a water-based perfume and test its stability. Stability is measured by average diameter, standard deviation, and zeta potential. The nanoemulsion is made using PEG-40 HCO surfactant with the atomization technique. Stability was tested by measuring the average diameter and standard deviation on day 0 and after 120 days of storage. In addition, heating tests were conducted at temperatures of 35°C, 40°C, and 45°C. The results showed that after 120 days of storage, there was an increase in the average diameter and a widening of the size distribution. This was due to the Ostwald ripening phenomenon, whereby smaller nanoemulsion molecules diffused and merged with larger ones. The zeta potential of the nanoemulsion was low (-6.6 to -8.1 mV), which was insufficient to prevent instability. However, when the nanoemulsion was heated, its average diameter decreased. Thermal restructuring occurs in the molecules that make up the nanoemulsion and the PEG-40 HCO molecules that encapsulate the nanoemulsion.